A review of the genus Sinodorcadion Gressitt, 1939 with description of three new species from China (Coleoptera: Cerambycidae: Lamiinae) - Xie, Guang-Lin; Shi, Fu-Ming; Wang, Wen-Kai (Zootaxa, 2013)
The genus Sinodorcadion Gressitt, 1939 is reviewed. Three new species, S. jiangi sp. nov., S. magnispinicolle sp. nov. and S. punctuscapum sp. nov., are described. A key to all known Sinodorcadion species (five) is presented.